2015
DOI: 10.1038/nature14867
|View full text |Cite
|
Sign up to set email alerts
|

Western US intermountain seismicity caused by changes in upper mantle flow

Abstract: Understanding the causes of intraplate earthquakes is challenging, as it requires extending plate tectonic theory to the dynamics of continental deformation. Seismicity in the western United States away from the plate boundary is clustered along a meandering, north-south trending 'intermountain' belt. This zone coincides with a transition from thin, actively deforming to thicker, less tectonically active crust and lithosphere. Although such structural gradients have been invoked to explain seismicity localizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 48 publications
2
37
2
Order By: Relevance
“…The residual is greatly reduced, with RMS 56 mGal, relative to the 78 mGal RMS of the observed Bouguer gravity and a 112 mGal residual associated with the starting model derived from receiver function cross‐correlation stacking. The residual gravity anomalies are likely dominated by asthenospheric mantle mass variations that our model does not account for (e.g., Becker et al, , ) and sphericity of the Earth, which produces anomalies that differ by up to tens of milligal from the Cartesian calculations used here on the scale of the conterminous U.S. The largest residuals appear to be dominated by a systematic pattern of greater asthenospheric mantle buoyancy in the west, resulting in residual anomalies mostly in the range of −150 to 50 mGal in the western U.S. but in the range −50 to 200 mGal in the east.…”
Section: Resultsmentioning
confidence: 75%
“…The residual is greatly reduced, with RMS 56 mGal, relative to the 78 mGal RMS of the observed Bouguer gravity and a 112 mGal residual associated with the starting model derived from receiver function cross‐correlation stacking. The residual gravity anomalies are likely dominated by asthenospheric mantle mass variations that our model does not account for (e.g., Becker et al, , ) and sphericity of the Earth, which produces anomalies that differ by up to tens of milligal from the Cartesian calculations used here on the scale of the conterminous U.S. The largest residuals appear to be dominated by a systematic pattern of greater asthenospheric mantle buoyancy in the west, resulting in residual anomalies mostly in the range of −150 to 50 mGal in the western U.S. but in the range −50 to 200 mGal in the east.…”
Section: Resultsmentioning
confidence: 75%
“…1d), suggesting that the historically-observed spatial distribution of large earthquakes may be a short-term feature. Vertical stress variations arising from dynamic support of the topography13 are unlikely to explain asymmetric seismic activity over this length scale. Here we present results of cosmogenic sampling of bedrock fault scarps along the southwest flank of the topographic high (Fig.…”
mentioning
confidence: 94%
“…However, GIA effects diminish exponentially away from the margin of the ice sheet, and hence, they have been argued to play a minimal role south of the hinge line (James & Bent, ; Kreemer et al, ; Wu & Johnston, ). Recent studies have also argued that dynamic topography resulting from radial mantle flow impact the occurrence of earthquakes away from plate boundary (Becker et al, ; Forte et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, GIA effects diminish exponentially away from the margin of the ice sheet, and hence, they have been argued to play a minimal role south of the hinge line (James & Bent, 1994;Kreemer et al, 2018;Wu & Johnston, 2000). Recent studies have also argued that dynamic topography resulting from radial mantle flow impact the occurrence of earthquakes away from plate boundary (Becker et al, 2015;Forte et al, 2010). Li et al (2007) calculated Coulomb stresses likely to arise from the presence of a lithosphere-craton boundary and found that regions of high Coulomb stress correlated with seismically active regions in CEUS, indicating that lateral variations of lithospheric structure is important for the occurrence of seismicity in the CEUS.…”
Section: Introductionmentioning
confidence: 99%